2016
DOI: 10.4103/1817-1737.173194
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding childhood asthma in Saudi Arabia

Abstract: OBJECTIVE:Assessing the knowledge and awareness of the Saudi society about bronchial asthma in children.METHODS:Structured questionnaires were randomly distributed to 1039 Saudi Arabians in May 2014 at Jeddah, Riyadh, and Dammam.RESULTS:The awareness of bronchial asthma questions showed that 67% of total sample thought that it could be a fatal disease, and only 13.2% thought that there is a difference between bronchial asthma and chest allergies in children. 86.1% thought that the symptoms of bronchial asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Results of this survey were compared to previously reported survey data conducted by Al-Harbi et al during the 2014 asthma awareness campaign in Saudi Arabia which also implemented the modified asthma knowledge questionnaire. 11 Asthma Knowledge Score Generation A numerical scoring system based on 25 points from the second portion of the survey was devised to evaluate asthma knowledge. The composite asthma knowledge score was calculated by giving correct answers a score of 1 and incorrect or "do-not-know" answers a score of 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of this survey were compared to previously reported survey data conducted by Al-Harbi et al during the 2014 asthma awareness campaign in Saudi Arabia which also implemented the modified asthma knowledge questionnaire. 11 Asthma Knowledge Score Generation A numerical scoring system based on 25 points from the second portion of the survey was devised to evaluate asthma knowledge. The composite asthma knowledge score was calculated by giving correct answers a score of 1 and incorrect or "do-not-know" answers a score of 0.…”
Section: Methodsmentioning
confidence: 99%
“…11 This initial study concluded that asthma knowledge needs to be improved in the general population. 11 In order to follow-up on these findings, this study aims to use a modified Structured Asthma Knowledge Questionnaire to evaluate the effectiveness of the annual Saudi asthma awareness campaigns during 2014-2019, with an additional focus on childhood asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Another important point to make is that this overview leaves room for treatments that are not always considered in the clinic. The first is nutritional support . Indeed, there is little to no evidence that particular nutrients can support either phase of a vitiligo cure.…”
Section: Commentarymentioning
confidence: 99%
“…As we learn more about signaling and the role of critical nutrients in processes important to cellular biochemistry, nutrition can become a factor in the healing process. The second is psychological support . It can be helpful for patients to share experiences and receive counseling either through professional help, or by patient support groups.…”
Section: Commentarymentioning
confidence: 99%
“…In [28], a comparative study investigated SVM and Decision Tree C4.5 models using 17658 self-collected documents. The results indicated that Decision Trees Model has more accurate classification than SVM when dealing with the Arabic textual Data.…”
Section: B Related Work In Arabic Text Categorizationmentioning
confidence: 99%